Technological Needs of Women in Dairying - K. Uma Rani, (Journal of Agricultural Extension Management, 2025)
Women play an active role in tasks related to animal husbandry. Rearing the milch cattle, poultry, goatery, sheep rearing are some of the livestock enterprises in which women are actively involved to supplement the income of their families. In many places the entire management of the livestock, particularly in dairying, is done by women alone. The present study examines the profile of the women involved in dairying, their awareness about the recommended practices and the technological needs expressed by them to improve their information base. The study highlights the need for training these women on certain critical dairy husbandry practices